A formação de professores de língua portuguesa e a educação lingüística: um estudo de caso - Gomes, Cláudia Santos do Nascimento (2008)
In the nationwide discussions about education and its improvement, There will always be several opinions around the professor and the role that he must do. Also the considerations that might occur regarding his professional graduation and a need of changing that guarantees the pleasant seizing in basic education in order to graduate people who are really aware of their citizenship. This writing focus on the question to the graduating from the professors of the Portuguese language, its basic education about linguistic education using the methology of research Case study Research , and focusing on a college of licensing in its Letras Course. To accomplish the intended purposes, we have heard so many voices that unite he universe of Letras Course of case , since the official documents from Ministry of Education towards the graduation of the professors of the Portuguese language, going through voices of the graduating and graduated professors who already work as student body in basic education, until we reach the course itself analyzed for the Letras Course s Educational Project and Program Teaching. After analyzing data, the results showed that, the Letras Course, the case analyzed, needs articulations in the speech of regulations on professors of the Portuguese language, and a suitable structure focusing on the Linguistic Education, which builds the profile acquired from the professor in basic education in the actionreflexion